Manajemen Berbasis Madrasah Sebagai Penunjang Mutu Pendidikan - Ramadhani, Safira Hartiana; Afiful Ikhwan (Tahta Media Group, 2024)
This research aims capture the efforts of Madrasah Based Management support the quality of education. This research was conducted at MI Kresna Mlilir on Ponorogo-Madiun street Ds. Mlilir Kec. Dolopo Kab. Madiun. The method used is qualitative-descriptive. Data collection using online literature studies as well as related and accredited journals. The effectiveness of the use of Madrasah based management is proven to support the quality of education at MI Kresna Mlilir, as seen in the students who are in the Madrasah many as 727 students. Making the best use of resources as well as possible in the Madrasah with the holding of training, meeting or musyawarah reguraly, budget funds that can meet the facilities and infrastructure of the Madrasah, will relize a good quality of education. So the output of Madrasah based management, students can carry out learning activities and achieve according to their abilities. Learning activities and achieve according to what abilities each has. Each with the caracter of students builts in the Madrasah environment.